Analisis Shear Strain dan Kerusakan Bangunan Akibat Gempa Bumi di Kecamatan Gading Cempaka dan Ratu Agung Kota Bengkulu - Kurnia Lestari; Muchammad Farid; Afrizal Mayub (University of Bengkulu, 2018)
ABSTRACT [The Analysis of Shear Strain and Building Damage due to Earthquake at Gading Cempaka and Ratu Agung District in Bengkulu City]. The aims of this research are to: (1) determine and mapping the distribution of shear strain values, (2) correlate between shear strains with building damage Gading Cempaka and Ratu Agung caused by earthwuake at sub district in Bengkulu city. Microtremor data were taken at 108 observation points then analyzed using HVSR method to obtain amplification factor and dominant frequency values..The result showed that shear strain value of Gading Cempaka and Ratu Agung sub district in Bengkulu city are relatively heterogeneous although in the same geological formation type. The earthquake in 2007 is estimated to be 3.38% potential to deform the land surface in the form of fractures and settlements and 96, 62% potentially experience shocks due to waves and vibrations due to earthquake. The earthquake of 2000 estimated that almost the entire area of Gading Cempaka and Ratu Agung has the potential to experience shocks due to waves and vibrations due to earthquake that is equal to 97% while potentially liquefaction (ambles) occurs by 3%. The correlation between shear strain with the damage of buildings due to earthquake shows the relationship is directly proportional to the function y = 15267x + 26.219 with the coefficient of resgression of = 0.671. Keywords: Earthquake; HVSR method; microtremor; shear strain.